Do Reorganization Costs Matter for Efficiency? Evidence from a Bankruptcy Reform in Colombia - Gine, Xavier; Love, Inessa (2012)
An efficient bankruptcy system should liquidate nonviable businesses and reorganize viable ones. The importance of this filtering process has long been recognized in the literature; the typical reason advanced for its failure has been biases (in codes or among judges). In this paper we show that bankruptcy costs can be another source of such filtering failure. We illustrate this with the Colombian reform of 1999. Using data from 1,924 firms filing for bankruptcy between 1996 and 2003, we find that the prereform reorganization proceedings were so inefficient that the bankruptcy system failed to separate economically viable firms from inefficient ones. In contrast, by streamlining the reorganization process, the reform contributed to the improvement of the selection of viable firms into reorganization. In this sense, the new law increased the efficiency of the bankruptcy system in Colombia.